Patient Satisfaction with Anesthesia Care After Curative Surgery for Neoplastic - Carvalho, Beatriz (2019)
Introduction: Satisfaction is an important measure for the evaluation of patient care and a significant tool for promoting improvements in clinical practice. We aimed to evaluate the association of quality of recovery and anesthesia related factors with patient satisfaction with anesthesia care (PSAC) after curative neoplastic surgery. Material and Methods: An observational, prospective study was performed in patients scheduled for neoplastic curative surgery.PSAC was evaluated on day 3 after surgery using a five-point Likert scale, and patients were grouped according to their score: those with Complete Satisfaction who rated 5 points, and those with Incomplete Satisfaction who rated <5. Perioperative demographic data, type of anesthesia and Quality of Recovery 15 score (QoR-15) were recorded and evaluated in both groups. The QoR-15 was performed before surgery (T0) and 24 hours after surgery (T1). Results: One hundred thirty-three patients of the 148 total included completed the questionnaires. Completed satisfaction was observed in 85% of the patients and was more frequent in patients submitted to general anesthesia (p=0.014). When comparing the total QoR-15 score by groups, there were no differences at both T0 (130vs126.6, p=0.932) and T1 (114 vs118,5, p=0.233). At T1, the QoR-15 showed that patients with incomplete satisfaction felt less rested (9vs7, p=0.041) and more worried and anxious (10 vs 8, p=0.040). Discussion and Conclusion: In our study, we found a global high rate satisfaction with anesthesia care in neoplastic patient, which was increased in those submitted to general anesthesia. Patient satisfaction with anesthesia care was not related with the QoR-15.